2015
DOI: 10.1016/j.ijsolstr.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Bounding surface modeling of sand with consideration of fabric and its evolution during monotonic shearing

Abstract: a b s t r a c tThis paper presents a bounding surface plasticity model for sand that considers fabric and its evolution during monotonic shearing. The model is based on critical-state soil mechanics. The bounding surface controls sand stiffness through a relationship that depends on the distance from the current state to the bounding surface calculated using a rigorous algorithm. Dilatancy, which measures the plastic volume change caused by plastic shear deformation, is captured through a newly introduced phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…An inclusion of the fabric descriptor in the anisotropic model is necessary to reflect the influence of the fabric on the dilatancy and hardening of the anisotropically consolidated soils. Similar approaches have been recently applied to the constitutive modeling of sands, as reported by previous studies . In particular, attempts have been made recently by Yang et al to address the dilative‐contractive‐dilative pattern observed in preceding experiments.…”
Section: Model Responses Against the Experimental Datamentioning
confidence: 74%
“…An inclusion of the fabric descriptor in the anisotropic model is necessary to reflect the influence of the fabric on the dilatancy and hardening of the anisotropically consolidated soils. Similar approaches have been recently applied to the constitutive modeling of sands, as reported by previous studies . In particular, attempts have been made recently by Yang et al to address the dilative‐contractive‐dilative pattern observed in preceding experiments.…”
Section: Model Responses Against the Experimental Datamentioning
confidence: 74%
“…Up until now, constitutive models have been developed based on various concept, including the incremental theory [19], fractal theory [20,21], shear strain and kinematic hardening theories [8,16,22] , and the bounding surface plasticity [7,12,23]. Some of the models [8,14,23] can simulate the real stress strain behaviour but are complex, whereas others [6,12] are relatively simple but cannot take into account the deformation and degradation of granular soils under complicated loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the models [8,14,23] can simulate the real stress strain behaviour but are complex, whereas others [6,12] are relatively simple but cannot take into account the deformation and degradation of granular soils under complicated loading conditions. Most importantly, these models [7,16] can only simulate the cyclic behaviour of granular soils for very limited loading cycles, say less than 100 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution rule in Equation conforms to the concurrent condition of the fabric according to ACST. A similar fabric evolution rule was also used in previous studies . To simulate the “softening”‐type evolution of fabric norm F with shear strain, as observed in dense sand sheared under drained conditions, one may modify the term of F in Equation by linking fabric evolution with the dilatancy of the soils; more details can be found in Yang et al…”
Section: Acst Integrated With a Hypoplastic Modelmentioning
confidence: 99%
“…Although the uniqueness of the critical state line (CSL) has been a subject of debate over many years, it tends to be corroborated by the increasing and consistent evidence from both experimental studies and discrete element method (DEM) simulations . Because of the paramount role of critical state theory in the development of constitutive models, the ACST framework has been adopted to develop various anisotropic models for granular soils …”
Section: Introductionmentioning
confidence: 99%